Spatial distribution of atomic and ion hydrogen flux and its effect on hydrogen recycling in long duration confined and non-confined plasmas. (August 2017) - Kuzmin, A.; Zushi, H.; Takagi, I.; Sharma, S.K.; Kobayashi, M.; Hirooka, Y.; Onchi, T.; Hanada, K.; Yoshida, N.; Nakamura, K.; Fujisawa, A.; Idei, H.; et al.
Highlights: Spatial distribution of the hydrogen wall irradiation fluxes has been directly measured for the first time in different types of long duration discharges with permeation and Langmuir probes. Radial distributions of atomic and ion fluxes are measured along the major radius inside the plasma side and behind the radiation shield on the midplane. The main irradiation flux to the PFCs originates from the radially diffusing plasma in the main volume of the plasma vessel. Beyond the PFC inside the closed port section ion flux can be completely neglect, irradiation is dominated by the atomic hydrogen flux. The atomic flux profile behind the PFC is almost constant at ∼2 ×10 18 H/s/m 2 . Abstract: In order to understand the atomic hydrogen distribution in different kinds of plasma and its influence on the recycling, two kinds of plasmas were used: non-confined annular electron cyclotron resonance (ECR) and confined long duration plasmas. The permeation probes are used to measure directly the atomic hydrogen flux at several poloidal positions. The permeation through metals due to the ion and atom component of the hydrogen flux to the wall is indistinguishable. To estimate the contribution of the ions directly, Langmuir probes were used. The Гinc profile behind the plasma facing components (PFCs) is almost constant, ∼2 ×10 18 H/s/m 2 .